THE FACTORS IMPACTING OVER ORGANIC PRODUCT’S MARKET: A STUDY OF KUMAUN REGION OF UTTARAKHAND - Garg, Vipul; Kumar, Krishan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Since ancient times, India has employed the organic farming technique, which is primarily concerned with producing agricultural products that are sustainable in a clean, unpolluted environment. In order to achieve the necessary agricultural production for human consumption, organic production methods make use of natural resources, maintaining the ecosystem and ecology alive and well. Using naturally occurring resources as inputs, such as organic wastes, farm, animal, and crop wastes, aquatic wastes, other biological materials, and beneficial microbes, is the environmental focus of organic production. Biofertilizers and biocontrol agents are used to release nutrients into crops and shield them from insect pests and diseases in order to increase agricultural productivity. It is imperative that farms move to organic practices. India, a nation that depends heavily on agriculture, must take measures to address the issue of its rapidly expanding population. Although there has been a noticeable movement in people's knowledge of organic food, it appears to be quite gradual. The cultivation of organic crops using the organic farming technique is gaining steam on a global scale. To achieve sustained food, livelihood, and environmental security, a range of alternatives to chemical intensive agriculture must be developed. The present study is an Exploratory cum Descriptive Research in nature with a sample size of 200 customers and various statistical tools such as frequency distribution, percentage, arithmetic mean and general linear Univariate model used. The respondents from different age group, different qualifications and others agreed that there should be an immediate improvement in the product accessibility in the market and the government as well as the producers, should play a key role in it. The study concludes that Organic product’s Market availability needs to improve from Govt. as well as producers both.